The Efectivity Of Core Stability Exercise AndMckenzie Exercise To Improving Activity Daily LivingOf The Tailors With Miogenic Low Back Pain ComplaintsAt Tambong Village District Klaten - Saputri, Oktaviari Dwi, Yulisna Mutia Sari, SSt.FT., M.Sc (), Totok Budi Santoso , S.Fis , MPH (2016)
Background: One of the many events musculoskeletal disorders including the complaint or pain in the low back pain (NPB). Miogenic LBP is pain associated with how the bones, ligaments and back muscles work. The pain would be a problem if affects the way we live or interfere with daily activities in life. There are different modalities of physiotherapy intervention in handling LBP, one of which is "Back Exercise", among which Mc Kenzie Exercise. In the process, there is a method known for its "Core stabiliy exercise" (CSE). CSE is a synergistic activation that includes the muscles of the core muscles of the trunk. Purpose: To determine the effect of CSE and McKenzie Exercise to increased functional activity in the tailors with Miogenic LBP complaints and differences in the effect of both. Aims of Research: Getting the evidence of benefits and know the differences of Core Stability Exercise (CSE) and McKenzie Exercise in improving functional activity in patients with Miogenic LBP. Methods: The study is quasi-experimental with two groups approach the pre and post test experimental design. The sampling technique used purposive sampling, as many as 20 respondents. The research instrument used ODI (Oswestry Disability Index). The statistical test used was Wilcoxon test and Mann Whitney test. Results: Statistical test results, the group treated with CSE obtained p-value of 0.005. The treatment group with McKenzie Exercise obtained p-value of 0.016. Meanwhile, from the differences were obtained p-value 0.813. Conclusion: There is the effect of CSE and McKenzie Exercise to increased functional activity in the tailors with miogenic LBP complaints and there is no difference in the results of both.